B Cells and Functional Antibody Responses to Combat Influenza - Lofano, Giuseppe; Kumar, Arun; Finco, Oretta; Del Giudice, Giuseppe; Bertholet, Sylvie (Frontiers in Immunology, 2015)
Vaccination against influenza (Flu) is the most effective way to protect the population. Current vaccines provide protection by stimulating functional B- and T-cell responses, however, they are poorly immunogenic in particular segments of the population and need to be reformulated almost every year due to the genetic instability of the virus. Next generation Flu vaccines should be designed to induce cross-reactivity, confer protection against pandemic outbreaks, and promote long-lasting immune responses among individuals at higher risk of infection. Multiple strategies are being developed for the induction of broad functional humoral immunity, including the use of adjuvants, heterologous prime-boost strategies, and epitope-based antigen design. The basic approach is to mimic natural responses to influenza virus infection by promoting cross-reactive neutralizing antibodies that directly prevent the infection. This review provides an overview of the mechanisms underlying humoral responses to influenza vaccination or natural infection, and discusses promising strategies to control influenza virus.